Knowledge, Awareness, and Practice Among Students in UTHM Pagoh on Dengue Fever - Hashim , Shazana; Rusli, Nur Izzati Izni; Mohd Rashidi, Nur Fatin Nadiah; Ashmuni, Nurul Hidayah (Multidisciplinary Applied Research and Innovation, 2021)
This technical paper is about the level of awareness, knowledge, and practice among Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh students on dengue as the number of cases and death keeps increasing day by day and yet there is still no cure. Moreover, fogging has been done for every semester in Pagoh residential college. The main objective of this study is to measure the level of knowledge, awareness and practices about dengue fever among UTHM Pagoh's students as well as to analyze the relationship between them. In this paper, a cross-sectional survey among 200 diploma and degree students from UTHM Pagoh was conducted using standard questionnaires. Data collected was analyzed using multiple linear regression with the use of statistical software SPSS version 26. The result shows that the students possessed an average knowledge, awareness, and practices on dengue with a positive weak relationship between them by the result of r² which is 0.084. Further research needs to be conducted to find an effective way to increase the level of knowledge, awareness, and practices among UTHM students.